Treatment Utilization and Medical Problems in a Community Sample of Adult Women With Anorexia Nervosa - Brodrick, Brooks; Harper, Jessica A.; Van Enkevort, Erin; McAdams, Carrie J. (Frontiers in Psychology, 2019)
Anorexia nervosa has a prolonged course of illness, making both defining recovery and determining optimal outpatient treatments difficult. Here, we report the types of treatments utilized in a naturalistic sample of adult women with anorexia nervosa in Texas. Participants were recruited from earlier studies of women with anorexia nervosa (AN-C, n = 28) and in weight recovery following anorexia nervosa (AN-WR, n = 18). Participants provided information about both their illness and treatments during their most severe period (severe period) as well as during the two to six years following original assessments (follow-up period). New follow-up groups were defined based on current clinical status (continued eating disorder, AN-CC; newly in recovery, AN-CR; sustained weight-recovery, AN-WS), and clinical utilization was compared across groups. There were no differences in groups related to symptoms or treatments utilized during the severe-period. During the follow-up period, intensive outpatient programs were utilized significantly more by the AN-CC group than the other groups, and dietitians were seen significantly less by the AN-WS group. Medical complications related to the ED were significantly more common in the AN-CC group. All groups maintained similar levels of contact with outpatient psychiatrists, therapists, and primary care physicians.